A comparative evaluation of post placental intrauterine contraceptive device (IUCD) insertion between normal delivery and caesarean section - Sarkar, Sharmistha; Paul, Dhruba Prasad; Ray, Jayanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Adverse maternal and perinatal outcomes are related to pregnancies spaced too closely together. Objective of present study was to compare the expulsion rate and complications between post placental IUCD insertion between caesarean section and vaginal delivery. Methods: This study was a prospective comparative study conducted in the department of Obstetrics and Gynecology, at Agartala Government Medical College over 1.5 Years (January 2016-June2017) All cases at term pregnancy delivering by caesarean section and vaginal delivery were divided into two different groups. Sample size of 105 in each group. Subjects recruited from-obstetrics OPD and casualty of Agartala Government Medical College (AGMC) and GB Pant Hospital expulsion rate and complications. Comparative evaluation of Expulsion rate and complications following post placental IUCD insertion between caesarean section and vaginal delivery at the end of six months, one year and one and half year. Results: There was no significant difference in either complications between the two groups (P value-.913) or outcomes (p value-.035). Expulsion rate 18.2% following vaginal delivery compared to those with intracaesarean insertion i.e 3.8%. Conclusions: The complications associated with postplacental Intrauterine device insertion is insignificant, still the awareness, acceptance and continuation are very low. Therefore Information, education Communication activity by the field workers must be enhanced to overcome this knowledge gap.